Effect of Chloromequat, Daminozide, Ethepon and Maleic hydrazide on certain vegetative characters of cardamom (Elettaria cardamomum Maton) seedlings - KUMAR, R NAIDU, SIDDAGANGAIAH SIDDAGANGAIAH, V KRISHNA (Journal of Spices and Aromatic Crops, 1993)
The effect of application of growth regulators such as Maleic hydrazide, Daminozide (Alar), Chloromequat (Cycocel) and Ethepon (Ethrel) on growth and development of cardamom (Elettaria cardamomum) seedlings of various age groups was studied. Maleic hydrazide (250 ppm), Daminozide (500 ppm), Chloromequat (250 ppm) and Ethepon (100 ppm) siginificantly enhanced tiller production and other vegetative characters when applied on 7 month old seedlings. These treatments were economical based on cost-benefit ratios that were worked out.